Dehydration behavior and kinetics of kurnakovite under microwave irradiation - Senberber, Fatma Tugce; Yildirim, Meral; Ozdogan, Iklim Nergiz; Kipcak, Azmi Seyhun; Derun, Emek (Tubitak Scientific & Technological Research Council Turkey, 2017)
In this research, the dehydration behavior of kurnakovite was studied under microwave irradiation. The kinetic parameters of the dehydration reaction were determined using different kinetic models. Kurnakovite was characterized by the techniques of X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM) before and after the dehydration process. According to the results, kurnakovite was identified as a compound with the powder diffraction file (pdf) number 00-024-0700 before the dehydration process and after the dehydration process amorphous formations were observed. Moreover, FT-IR results showed that dehydration was completed successfully because of the disappearance in the band values of structural water. The dehydration process was ended at 25, 20, and 15 min for the power levels of 360, 600, and 800 W, respectively. Among the models, the two-term exponential model best fits the drying experimental data. For the activation energy calculation, the Page model best fits the experimental data and was found as 9.92 W x g(-1).
Keywords: Dehydration; kinetic; kurnakovite; microwave; DRYING KINETICS; INDERITE; Chemistry; Engineering